2012
DOI: 10.1118/1.4760993
|View full text |Cite
|
Sign up to set email alerts
|

Relation between plaque type, plaque thickness, blood shear stress, and plaque stress in coronary arteries assessed by X‐ray Angiography and Intravascular Ultrasound

Abstract: Purpose: Atheromatic plaque progression is affected, among others phenomena, by biomechanical, biochemical, and physiological factors. In this paper, the authors introduce a novel framework able to provide both morphological (vessel radius, plaque thickness, and type) and biomechanical (wall shear stress and Von Mises stress) indices of coronary arteries. Methods: First, the approach reconstructs the three-dimensional morphology of the vessel from intravascular ultrasound (IVUS) and Angiographic sequences, req… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…Such characteristics are essential for the clinical diagnosis since to date it is the only modality enabling the accurate morphological segmentation of both vessel membranes (lumen and media) and the assessment of the plaque type in vivo [5,6]. Additionally, when IVUS is fused with X-ray projections, three dimensional plaque quantification and reconstruction can be obtained [7,8] (Fig. 2).…”
Section: Clinical Backgroundmentioning
confidence: 99%
“…Such characteristics are essential for the clinical diagnosis since to date it is the only modality enabling the accurate morphological segmentation of both vessel membranes (lumen and media) and the assessment of the plaque type in vivo [5,6]. Additionally, when IVUS is fused with X-ray projections, three dimensional plaque quantification and reconstruction can be obtained [7,8] (Fig. 2).…”
Section: Clinical Backgroundmentioning
confidence: 99%
“…IVUS images have several anatomical features, including the lumen, external elastic membrane (EEM), and plaque materials. Several studies have proposed methods for combining IVUS and angiography images for 3D reconstruction of coronary arteries [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] ; however, these approaches were focused on non-bifurcated vessels. Some studies have performed 3D reconstruction of bifurcations but relied on computed tomography (CT) images to correct the IVUS frame orientation, limiting their clinical applicability 24,25 .…”
mentioning
confidence: 99%
“…All such studies of vessel wall mechanics use intravascular ultrasound (IVUS) combined with FEA to compute wall stress. For example, a comprehensive analysis was performed by Balocco et al, 30 which showed an inverse relationship between shear stress and wall stress in 10 patients with plaques, an observation that was recently confirmed by Fan et al 31 Liang et al 32 used a fluid-solid interaction model in diseased vessel segments of 4 patients and identified increasing stress concentrations with thinning of the cap, and the presence of microcalcifications, as observed previously. 33 Hence, these invasive studies confirmed observations from the noninvasive ones that local stress concentrations occur during plaque development.…”
Section: Plaque Stress Concentrations As a Mechanism For Rupturementioning
confidence: 86%